Carbon Pools of Indigenous and Exotic Trees Species in a Forest Plantation, Prachuap Khiri Khan, Thailand - Ponthep Meunpong; Chongrak Wachrinrat; Bunvong Thaiutsa; Mamoru Kanzaki; Kongsak Meekaew (Agriculture and Natural Resources, 2010)
The carbon pool was evaluated in a forest plantation in Kui Buri district, Prachuap Khiri Khan province, on peninsular Thailand. The study was conducted in native and exotic tree species plots, when the trees were aged 14-15 y. The above- and below-ground biomass of each tree species was evaluated. Plant and soil carbon concentrations and carbon pools were estimated. The total biomass of the stands aged 15 y ranged from 51.04 to 291.25 t ha-1. On average, woody tissue (stem, branches and roots) made up 95% of the stand biomass. The fast-growing species, Acacia crassicarpa and Azadirachta indica, stored more carbon in biomass (177.12 and 91.37 t ha-1). These results indicated that the efficiency of carbon storage for all stands of all tree species depended largely on the biomass. The carbon pool in the mineral soil layer (0-50 cm depth) ranged from 44.49 and 62.64 t ha-1. In addition, the carbon content in the surface soil was higher than in sub-surface levels for every treatment. The results suggested that A. crassicarpa and A. indica were the most appropriate species for rapid carbon sequestration, with native tree species, such as Tectona grandis and Xylia xylocarpa, being alternative choices.